MEDIA BARU DALAM PELAYANAN PUBLIK: (Sosial Media dalam Pelayanan Publik oleh OMBUDSMAN RI Bengkulu) - FITRIA YULIANI; rekho adriadi; linda safitra (Commed : Jurnal Komunikasi dan Media, 2020)
Along with level of social media fame that higer than before, we cannot deny that now there is an expansion of social media "functions", where the social media is not only used as a medium of self-existence, but also the existence of groups, institutions and state institutions. Used not only for individual interests, but also for economic, social, political, and cultural interests. One of the social media functions “now” is the function of public services, where the social media is used as a medium of public service by institutions and state institutions like Ombudsman RI Bengkulu. Digital-based services through the internet network are carried out by Ombudsman RI Bengkulu as a way to reach the community. Such as through Facebook, Twitter, Youtube and Instagram. Digital-based services via the internet by the Ombudsman RI Bengkulu can be said a manifestation of the Ombudsman service innovation to the public. Therefore it is interesting to see about how far the social media is used by the Indonesian Ombudsman Bengkulu for public service purposes. This study is a qualitative study that seeks to analyze and describe the use of Instagram in public services by the Ombudsman RI Bengkulu. The results showed that social media, by the Ombudsman RI Bengkulu, was used as a medium for socializing and raising complaints in the process of public service. Besides being used as a media for public services, there are positive and negative impacts arising from the use of social media in the public service process by the Ombudsman RI Bengkulu. However, the use of social media is considered effective and is considered to be able to facilitate the process of public service, besides that it is also a manifestation of the diffusion of innovation in the public service process by the Indonesian Ombudsman Bengkulu. Keywords: Utilization, Social Media, public services, RI Ombudsman Bengkulu, Innovation